TREX - Haraty, Ramzi A. (2005)
Summary form only given. Our work demonstrates the process of extracting the temporal references from the texts. This procedure is highly dependable on the stemming process. A list of all the temporal references is used. The type of the temporal word decides the procedure to treat this word and gives the importance of this temporal reference. These conditions, with the help of the stemmer, produced an excellent result of 95% as precision and of 91% as recall.